SPATIALIZATION OF OCCURRENCES ON THE DEPARTMENT OF ENVIRONMENTAL PROTECTION POLICE (COPPA), THROUGH THE USE OF GEOTECHNOLOGIES - Sant'Ana, Rosana Maria Santos; Carvalho, Silvana Sá de; Jesus, Arnaldo Bispo de (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
The purpose of this article is to show the spatial distribution of occurrences registered in Environmental Police Company in Salvador and more 12 cities of its Metropolitan Region in the year 2012, using Geotechnologies. Initially, data was collected and inserted into a Geographical Information System-WEB (GIS-WEB). These records contained a nearly geographic location of the occurrence. Thus it was possible to specalize them and systemaize them using an specific geoprocesing software ”“ the ArcGIS. Lately the Kernel density Estimator was apllied to data to become possible visualizing the spots of higher concentration of point. Then it was possible to idenify and analyze areas with larger rates of requests upon social insects, sylvan animals and even environmental crimes denounces. It is expected that the resulting maps can give a support on the planning of actions to this company.